Peri‐Implantitis versus Periodontitis: Functional Differences Indicated by Transcriptome Profiling. (11th September 2012) - Becker, Stephan T.; Beck‐Broichsitter, Benedicta E.; Graetz, Christian; Dörfer, Christof E.; Wiltfang, Jörg; Häsler, Robert
<x xml:space="preserve">Abstract</x> Background Periodontitis and Periimplantitis are oftentimes discussed as one entity, which is reflected by therapeutical as well as by scientific approaches. It is unclear, to which extent the similarity of the clinical characteristics is attributed to similarities in the underlying disease mechanisms. Purpose The main objective of the study is to display if or how different periimplantitis and periodontitis are on the mRNA level, representing a high‐resolution map of disease‐associated events. Materials and Methods Aiming to describe the pathophysiological mechanisms in vivo, primary gingival tissue from 7 periimplantitis patients, 7 periodontitis patients and 8 healthy controls was employed in order to generate genome wide transcriptome profiles. Results On the basis of quantitative transcriptome analysis, we could show that periimplantitis and periodontitis exhibit significantly different mRNA signatures. Additionally we present a disease associated mRNA profile, which displays potential periimplantitis disease mechanisms. A gene ontology analysis revealed various pathways, supporting the hypothesis of periimplantitis being a complex inflammatory disorder with a unique pathophysiology. While in periimplantitis tissue the regulation of transcripts related to innate immune responses and defense responses were dominating, in periodontitis tissues bacterial response systems prevailed. Conclusions Taken together, our results suggest considering periimplantitis and periodontitis as disease entities with shared as well as with distinct features, which should be reflected on the therapeutical as well as on the scientific level.